Community Awareness of NPA-VAWC in Ending Violence Against Children - Rehema Magesa (Journal of Social and Community Development, 2026)
Violence against children remains a major global and national concern, undermining children’s safety, development, and well-being. In response, the Government of Tanzania implemented the National Plan of Action to End Violence Against Women and Children (NPA-VAWC) to strengthen prevention and response strategies. This study examined community awareness of violence against children and the level of awareness and participation in the implementation of the NPA-VAWC in Mbeya City Council. A mixed-method approach with a cross-sectional design was employed, involving 100 randomly selected community members and four key informants. Data were collected through questionnaires, interviews, and document review, and analyzed using descriptive statistics and content analysis. The findings revealed that while 96% of respondents were aware of violence against children, only 35% were aware of the NPA-VAWC. The overall awareness level was moderate, with 67% of respondents demonstrating medium awareness. The study concludes that limited awareness of national strategies constrains community participation and highlights the need for strengthened awareness campaigns and community-based education.